2015
DOI: 10.3390/su71115136
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Passive vs. Active Strategies for a School Building Design

Abstract: This paper presents a simulation study to reduce heating and cooling energy demand of a school building in Seoul Metropolitan Area, Korea. The aim of this study was to estimate the impact of passive vs. active approaches on energy savings in buildings using EnergyPlus simulation. By controlling lighting, the energy saving of the original school building design was found most significant, and increased by 32% when the design was improved. It is noteworthy that energy saving potential of each room varies signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…sustainable design in schools was a powerful predictor of children's environmental attitudes and behaviours, and that children attending schools designed for sustainability had more proenvironmental attitudes and behaviours than children in conventional schools (Wake and Eames, 2018, report similar ndings in New Zealand). e above study corroborates prior research recognizing the impact of sustainable design in schools on children's environmental learning (Newton, Wilks and Hes, 2009;Cole, 2013), and suggests that experiential learning via sustainability features at school, such as such as solar panels, use of recycled water and natural daylight, provides children with the opportunity to be mindful of, and to a ect, consumption of energy and water (Kang et al, 2015). Experiential education, such as learning in outdoor classrooms and schoolyard gardening, can also increase students' relationships with nature and their sense of contributing to action on sustainability issues (Wake, 2004;Wake and Birdsall, 2016).…”
Section: H a P T E Rsupporting
confidence: 85%
“…sustainable design in schools was a powerful predictor of children's environmental attitudes and behaviours, and that children attending schools designed for sustainability had more proenvironmental attitudes and behaviours than children in conventional schools (Wake and Eames, 2018, report similar ndings in New Zealand). e above study corroborates prior research recognizing the impact of sustainable design in schools on children's environmental learning (Newton, Wilks and Hes, 2009;Cole, 2013), and suggests that experiential learning via sustainability features at school, such as such as solar panels, use of recycled water and natural daylight, provides children with the opportunity to be mindful of, and to a ect, consumption of energy and water (Kang et al, 2015). Experiential education, such as learning in outdoor classrooms and schoolyard gardening, can also increase students' relationships with nature and their sense of contributing to action on sustainability issues (Wake, 2004;Wake and Birdsall, 2016).…”
Section: H a P T E Rsupporting
confidence: 85%
“…Likewise, Schneider (2003) showed that building age affects teacher evaluation of school facilities [70] (p. 20). It will be of interest to investigate if this pattern changes in newer schools on account of gradual incorporation of bioclimatic principles and the use of simulated passive building design strategies and active strategies for energy efficiency [73].…”
Section: Environmental Quality Of Existing School Facilitiesmentioning
confidence: 99%
“…40% of total energy and it's responsible for one-third of global greenhouse gas emissions (Wu H., Thomas 2007). One of the most effective strategies for reducing energy consumption and improving indoor air quality are passive strategies (Kang et al 2015). The passive strategies are characteristic for the premid-century architecture across the globe (Hootman 2013).…”
Section: Introductionmentioning
confidence: 99%